2022
DOI: 10.1038/s41467-022-34687-7
|View full text |Cite
|
Sign up to set email alerts
|

Enterotoxigenic Escherichia coli heat-labile toxin drives enteropathic changes in small intestinal epithelia

Abstract: Enterotoxigenic E. coli (ETEC) produce heat-labile (LT) and/or heat-stable (ST) enterotoxins, and commonly cause diarrhea in resource-poor regions. ETEC have been linked repeatedly to sequelae in children including enteropathy, malnutrition, and growth impairment. Although cellular actions of ETEC enterotoxins leading to diarrhea are well-established, their contributions to sequelae remain unclear. LT increases cellular cAMP to activate protein kinase A (PKA) that phosphorylates ion channels driving intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 95 publications
(132 reference statements)
0
6
0
Order By: Relevance
“…Anti-LT reactive antibodies have also been shown to modulate the severity of ETEC-associated illness in a CHIM [31], to protect against ETEC strains producing only LT in field studies, and to reduce the severity of ETEC-associated disease in general in the field [31,32,44]. Similarly, higher anti-CTB serum IgA titers are associated with a reduced risk of ETEC-attributable travelers' diarrhea and lower disease severity scores in U.S. travelers to Guatemala and Mexico [30,31,45]. This study also provides the first information on the systemic and mucosal immunogenicity of VLA1701.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-LT reactive antibodies have also been shown to modulate the severity of ETEC-associated illness in a CHIM [31], to protect against ETEC strains producing only LT in field studies, and to reduce the severity of ETEC-associated disease in general in the field [31,32,44]. Similarly, higher anti-CTB serum IgA titers are associated with a reduced risk of ETEC-attributable travelers' diarrhea and lower disease severity scores in U.S. travelers to Guatemala and Mexico [30,31,45]. This study also provides the first information on the systemic and mucosal immunogenicity of VLA1701.…”
Section: Discussionmentioning
confidence: 99%
“…GLP-1 binds to GLP-1R to generate cAMP, which activates PKA by binding to the PKA regulatory subunit, RIS or RIS. On the one hand, the catalytic subunit (C) of PKA is released from the PKA tetramer and phosphorylates NHE3 at Serine 552, reducing plasma membrane NHE3 expression [ 31 ]. On the other hand, it can reduce the expression of USP7 or USP10, increase the ubiquitination level of NHE3, enhance the endocytic transport of NHE3, and reduce the surface membrane abundance of NHE3, both of which can lead to a significant reduction in the total amount of NHE3 protein [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activated CREB transcription factor is then free to engage multiple cAMP-responsive elements (CRE, e.g ., 5’-TGACGTCA-3’) in the regulatory regions of approximately 4000 genes within the human genome. Not surprisingly, recent studies of transcriptional modulation by LT have revealed that it impacts the expression of hundreds of genes in intestinal epithelial cells ( 63 ).…”
Section: Importance Of Ceacam- E Coli Interactionsmentioning
confidence: 99%